Perbandingan Hasil Mozaik Foto Udara Menggunakan Aplikasi Desktop Agisoft Metashape dengan Aplikasi Cloud Computing Dronedeploy - Putu Sukrana; I Gede Yudi Wisnawa; I Wayan Krisna Eka Putra (Universitas Pendidikan Ganesha, 2023)
Agisoft is a desktop application-based software, while DroneDeploy is a cloud computing-based software. More accurate aerial photo mosaic results from the two software need to be ensured. This research aims to find out more accurate software from the results of aerial photo mosaics. The method in this research is to compare the processing time, the required cost, the accuracy of the distance, and the visual results of the aerial photo mosaic. The results of this study are the stages of processing aerial photos using Agisoft through six stages. Dronedeploy has a simpler stage, going through only three stages. Dronedeploy aerial photo mosaic distance accuracy comparison is superior with an accuracy of 97.44% to 99.65%, Dronedeploy's processing time comparison is faster with a time difference of 34 minutes, Agisoft's cost is cheaper with a cost difference of Rp 30,000, visual comparison of Dronedeploy aerial photo mosaic results superior to the edge of the roof of the house is neater